Jeopardizing quality at the frontline of healthcare: prevalence and risk factors for disrespect and abuse during facility-based childbirth in Ethiopia - Banks, Kathleen P (Health Policy Plan, 2018)
Disrespect and abuse (D&A) experienced by women during facility-based childbirth has gained global recognition as a threat to eliminating preventable maternal mortality and morbidity. This study explored the frequency and associated factors of D&A in four rural health centres in Ethiopia. Experiences of women who delivered in these facilities were captured by direct observation of client-provider interaction (N = 193) and exit interview at time of discharge (N = 204). Incidence of D&A was observed in each facility, with failure to ask woman for preferred birth position most commonly observed [n = 162, 83.9%, 95% confidence interval (95% CI) 78.0–88.5%]. During exit interviews, 21.1% (n = 43, 95% CI 15.4–26.7%) of respondents reported at least one occurrence of D&A. Bivariate models using client characteristics and index birth experience showed that women’s reporting of D&A was significantly associated with childbirth complications [odds ratio (OR) = 7.98, 95% CI 3.70, 17.22], weekend delivery (OR = 0.17, 95% CI 0.05, 0.63) and no previous delivery at the facility (OR = 3.20, 95% CI 1.27, 8.05). Facility-level fixed-effect models found that experience of complications (OR = 15.51, 95% CI 4.38, 54.94) and weekend delivery (OR = 0.05, 95% CI 0.01–0.32) remained significantly and most strongly associated with self-reported D&A. These data suggest that addressing D&A in health centres in Ethiopia will require a sustained effort to improve infrastructure, support the health workforce in rural settings, enforce professional standards and target interventions to improve women’s experiences as part of quality of care initiatives.